Examin the impact of e-procurement systems on supply chain efficiency - Waibi Gerald Grace (UCU, 2024)
Electronic procurement systems are highly significant aspect in business and they have affected a lot improving on supply chain efficiency in organizations situated in Kampala, Uganda. Through this research aimed to examine on the impact e-procurement systems on supply chain efficiency, this has been looked at in the background basing on global advancement through looking at how it has impacted organizations on a global land scale then on Africa level, East Africa and Uganda where we see how it was started to be integrated in various areas of the government easily at ministry of finance where it started from and spread to other ministries. The study looked at cost-effectiveness, and operational efficiency as one of the successes made by e-procurement. This study was conducted between April and August 2024, with a review of literature from 2019 to 2024, on the information of the organization in the study assessed various e-procurement techniques, including e-supplier management, e-invoicing, and e-payment and they have impacted on inventory management, cost reduction, risk management, supplier coordination, and lead times. Utilizing a qualitative approach through structured questionnaires given to procurement officers, supply chain managers, IT staff, and finance managers, the research found that e-invoicing and e-supplier management significantly improved procurement efficiency by reducing administrative overhead and enhancing supplier relationships. E-catalogues and electronic payment mechanisms, however, have had varying degrees of success. The findings imply that even if e-procurement technologies have, on the whole, increased supply chain efficiency, problems with adoption, employee resistance, and system integration still exist. Enhancing staff training, streamlining e-catalogues and e-tendering, resolving execution issues, and enhancing technology integration are among the recommendations. Future studies should examine the effects of future technologies like blockchain and artificial intelligence, the scalability of e-procurement in developing nations, difficulties facing SMEs, integration with corporate systems, and methods for guaranteeing data security and privacy-catalogues and electronic payment mechanisms, however, have had varying degrees of success. The findings imply that even if e-procurement technologies have, on the whole, increased supply chain efficiency, problems with adoption, employee resistance, and system integration still exist. Enhancing staffing levels, enhancing e-catalogues and e-tendering, and strengthening technological integration are among the suggestions